Clinical pathway interpretation of transurethral plasmakinetic resection of prostate for benign prostatic hyperplasia - Si-Yu YAN; Xing HUANG; Zheng CHEN; Lu YANG; Zhao-Hui JIA; Mou PENG; Xuan-Yi REN; Jing XIONG; Xiao-Dong LI; Xiao-Feng XU; Zhong-Yi SUN; Yong-Bo WANG; et al. (Yixue xinzhi zazhi)
Benign prostatic hyperplasia is the most common benign disease that causes urination dysfunction in middle-aged and elderly men, and is also the main cause of lower urinary tract symptoms. Transurethral plasmakinetic resection of prostate has been widely used in clinical practice for its good efficacy and safety. In order to further standardize the clinical application of this surgery, the National Health Commission published the initial Clinical Pathway Interpretation of Transurethral Plasmakinetic Resection of Prostate for Benign Prostatic Hyperplasia in 2019. In view of the limited content of this clinical pathway, using it as a blueprint, we have interpreted it and applied the ideas and methods of evidence-based medicine, aiming to provide a more detailed evidence supplement to help medical staff and managers better understand, grasp and correctly use this clinical pathway.